Relation of Homocysteine With Malondialdehyde and Dyslipidemia in Type 2 Diabetic Patients with Coronary Artery Diseases (Indian Journal of Forensic Medicine & Toxicology, 2020)
Diabetes mellitus(DM) is one of the most common chronic disorder widely prevalent throughout the world. DM is characterized by elevation of blood glucose (hyperglycemia). Hyperglycemia, with time, led to several serious macro and mircovascular complications. The purpose of study was to investigate the relation of Homocysteine(Hcy) with oxidative stress (malondialdehyde”MDA”) and dyslipidemia in type 2 diabetic patients with coronary artery diseases in comparison to patients of coronary artery diseases(CAD) without DM. Methods: The present study included 60 patients of coronary artery disease. Patients divided into two groups: group1 = 30 coronary artery disease patients without diabetic and group2 = 30 coronary artery disease patients with type2 diabetes. Homocysteine was estimated by competitive ELISA test using commercially available kit. MDA was estimated by colorimetric method. Lipid profiles were determined by using commercial available kits. Results: Plasma levels of Hcy and MDA in group1 and group2 were significantly higher (p<0.05) than controls. In group1 Hcy shows significant (P<0.05) positive correlation with MDA and Total Cholesterol (TC). Hcy shows no significant (p>0.05) positive correlation with very low density lipoprotein (VLDL), low density lipoprotein (LDL),and Triglyceride(TG). Hcy shows negative significant (p<0.05)correlation with high density lipoprotein( HDL). While in group2 Hcy shows significant (P<0.05) positive correlation with MDA, TC, VLDL, LDL and TG. Hcy shows negative significant (p<0.05)correlation with HDL. Hcy, MDA, TC, TG, LDL and VLDL were higher without significant in CAD diabetic patients than non-diabetic CAD patients. HDL was lower in diabetic coronary artery disease patients than non-diabetic coronary artery disease patients but without significant importance. Conclusion: In this study Hcy and MDA levels obtained were found to be positively correlated with dyslipidemia in patients in both groups. Hcy may be one of the cause for development and progress of macro- and microvascular disease. Hcy, MDA and dyslipidemia were higher in CAD with DM than CAD without DM this shows that hyperglycemia may be is another factor to increase atherosclerotic process.